Effect of firing temperature on the particles size of Gd2O3: Eu doped nanophosphors - Tamrakar, Raunak Kumar; Bisen, D P; Brahme, Neemta; Robinson, C S; sharma, B G (Recent Research in Science and Technology, 2012)
The paper reports that synthesis and characterization of Eu2+ doped Gd2O3 nanophosphors prepared by combustion synthesis. It has been reported that the effect of synthesis temperature on particle size dependence phenomenon of rare earth doped nanophosphors. The sample was characterized by XRD pattern and FTIR study. Synthesized sample shows cubic structure verified by the XRD results. Size of the particle was caculated by scherer equation the avarage size obtained 15, 23 and 55 at 4000C, 5000C and 6000C respectively. In this synthesis urea used as a fuel for created reducing atmosphere during sample preparation.